2014
DOI: 10.1080/03004430.2014.991723
|View full text |Cite
|
Sign up to set email alerts
|

Obesity prevention interventions in early childhood education and care settings with parental involvement: a systematic review

Abstract: Partnering early childhood education and care (ECEC) and the home together may be more effective in combating obesogenic risk factors in preschool children. Thus, an evaluation of ECEC obesity prevention interventions with a parental component was conducted, exploring parental engagement and its effect on obesity and healthy lifestyle outcomes. A search revealed 15 peer-reviewed papers. Some studies demonstrated positive weight changes, and secondary outcomes of changes in physical activity and healthy eating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
43
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 53 publications
(280 reference statements)
2
43
0
Order By: Relevance
“…Fourteen systematic reviews were considered eligible for the present Umbrella review. Of the 14 included reviews, seven stated obesity-related physiological outcomes, for example, Body Mass Index (BMI) as the primary outcome, with diet-related outcomes reported separately as secondary outcomes [ 38 , 39 , 52 , 53 , 54 , 55 , 56 ]. The other seven studies, addressed diet-related behaviours as the primary outcomes [ 23 , 41 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fourteen systematic reviews were considered eligible for the present Umbrella review. Of the 14 included reviews, seven stated obesity-related physiological outcomes, for example, Body Mass Index (BMI) as the primary outcome, with diet-related outcomes reported separately as secondary outcomes [ 38 , 39 , 52 , 53 , 54 , 55 , 56 ]. The other seven studies, addressed diet-related behaviours as the primary outcomes [ 23 , 41 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…A relatively small number of primary studies were excluded by the reviewers ( Table S3 : Characteristics of included systematic reviews). Reasons for ineligibility of some of the primary studies were no dietary outcomes reported or settings such as schools and Family Day Care [ 39 , 53 , 57 ]. The total sample size of the studies included in the individual reviews ranged between 260 children [ 60 ] to more than 18,000 [ 53 , 57 ] and centres caring for between six [ 60 ] and more than 1050 children [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations